Environmentally Friendly Non‐Metal Solar Photocatalyst C3N4 for Efficient Nitrogen Fixation as Foliar Fertilizer. Issue 26 (8th July 2020) - Liu, Yifan; Huang, Xiuying; Yu, Zirui; Yao, Lulu; Guo, Shanshan; Zhao, Weirong
Abstract: Photocatalytic nitrogen fixation based semiconductors has been expected to replace the traditional Haber‐Bosch process to synthesize nitrogen fertilizer for agricultural application. Polymeric carbon nitride (PCN) with the response to solar spectrum has been widely used. In order to improve its photocatalytic efficiency, the exfoliated carbon nitride (C3 N4 ) was prepared with a facile two‐step calcining method for nitrogen fixation. SEM/TEM results reveal that with the secondary thermal process, the exfoliated C3 N4 photocatalyst shows a porous appearance. The optimal catalyst with secondary calcination for 120 min exhibits large specific surface area of 206 m 2 ⋅g −1 and the photocatalytic activity for ammonium evolution is evidently enhanced to 4.20 times of PCN. Further, nitrogen adsorption systems with different adsorption sites were constructed based on first principles simulation analysis. The result indicated that N2 molecule was more likely to physically adsorb over the two‐coordinated nitrogen atom in the horizontal mode with an adsorption energy of −72.59 kJ⋅mol −1 . It provided reference for the further study of the N2 adsorption activity on the catalyst. This work developed environmentally friendly C3 N4 catalysts with more active sites to function as prospective "foliar fertilizer" system along with scavenger glycerol. Abstract : The exfoliated carbon nitride was synthesized by secondary calcination. As prepared catalysts exhibit high specific surface area and efficient transfer of photo‐induced carriers for the sake of the reduced thickness. Further, nitrogen adsorption with different sites was conducted via first principles simulations. The environmentally friendly materials were applied to nitrogen fixation and showed good photocatalytic performance, indicating that it can function as prospective "foliar fertilizer" system along with glycerol.